International investments in private equity asset allocation, markets, and industry structure - Cornelius, Peter 1960- (Academic Press, 2011)
How can private equity investors exploit investment opportunities in foreign markets? Peter Cornelius uses a proprietary database to investigate and describe private equity markets worldwide, revealing their levels of integration, their risks, and the ways that investors can mitigate those risks. In three major sections that concentrate on the risk and return profile of private equity, the growth dynamics of discrete markets and geographies, and opportunities for private equity investments, he offers hard-to-find analyses that fill knowledge gaps about foreign markets. Observing that despite the progressive dismantling of barriers investors are still home-biased, he demonstrates that a methodical approach to understanding foreign private equity markets can take advantage of the macroeconomic and structural factors that drive supply and demand dynamics in individual markets. Foreword by Josh Lerner Teaches readers how to investigate and analyze foreign private equity markets Forecasts private equity investment opportunities via macroeconomic and structural factors in individual markets Draws on data from a proprietary database covering 250 buyout and VC funds and 7,000 portfolio companies.
Includes bibliographical references (pages 279-288) and index
Keywords: Private equity; Investments, Foreign; Capital-investissement; Investissements étrangers; BUSINESS & ECONOMICS; Investments & Securities